Model Pembelajaran Read, Answer, Discuss, Explain, and Create (Radec) dalam Meningkatkan Keterampilan Berpikir Kritis Siswa di Sekolah Dasar - Rifa Pratiwi; Yullys Helsa (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
The RADEC (Read, Answer, Discuss, Explain, and Create) learning model is an innovative approach that aims to improve students' critical thinking skills in elementary schools. This study aims to explore the effectiveness of implementing the RADEC model in the context of elementary school learning and its impact on the development of students' critical thinking skills. The RADEC approach emphasizes active student involvement through five main stages: reading to build initial understanding, answering questions to test reasoning power, discussing to broaden perspectives, re-explaining concepts to deepen understanding, and creating products or solutions as a concrete manifestation of the critical thinking process. This study used a quantitative method with a quasi-experimental design and involved fifth grade students in a public elementary school. The instruments used were critical thinking tests and student activity observation sheets. The results showed that the implementation of the RADEC model significantly increased students' critical thinking skill scores compared to conventional learning models. In addition, students showed higher enthusiasm and learning independence during the learning process. These findings indicate that the RADEC model is not only able to build a stronger understanding of concepts but also encourages students to actively analyze, evaluate, and create ideas. Therefore, the RADEC model is recommended as an effective alternative learning strategy to improve the quality of learning and critical thinking skills of students at the elementary school level.